Interaction between Reproductive Hormones and Physiological Sleep in Women - de Zambotti, Massimiliano (J Clin Endocrinol Metab, 2015)
CONTEXT: The changing hormonal milieu around menopause is implicated in the development of sleep disturbances. No studies have assessed the association between concurrent physiological measures of sleep and serum hormone concentrations in perimenopausal women. OBJECTIVE: This study aimed to assess the interaction between physiological sleep and reproductive hormone measures in perimenopausal women. DESIGN AND PARTICIPANTS: This was a cross-sectional laboratory study of 33 perimenopausal women age 43–52 years (17 with no sleep complaints and 16 with a clinical diagnosis of insomnia). Eleven premenopausal women without sleep complaints (18–27 y), were included to determine whether hormone-sleep relationships differed depending on reproductive stage. MAIN OUTCOME MEASURES: Concurrent polysomnographic sleep indices and serum hormone levels (estradiol and follicle stimulating hormone [FSH]) were measured. RESULTS: FSH was positively associated with polysomnographic-defined wakefulness after sleep onset, and number of awakenings and arousals in perimenopausal women (P < .05) without sleep complaints independent of age, body mass index, and hot flashes. Similarly, FSH correlated with wakefulness after sleep onset and light N1 sleep in premenopausal women (P < .05). In contrast, in perimenopausal insomniacs amount of sleep correlated with anxiety and depression (P < .05) but not with FSH. Estradiol did not correlate with sleep in perimenopausal groups but correlated negatively with arousals in premenopausal women (P < .01). CONCLUSION: Our results suggest an interaction between the hypothalamic-pituitary-ovarian (HPO) axis and sleep-wake regulatory systems in pre- and peri-menopausal women without sleep complaints. There was no relationship between hormones and sleep in perimenopausal insomniacs, whose sleep may be influenced by other factors intrinsic to insomnia, such as hyperactivity, poor mood, and night-to-night variability.